2022
DOI: 10.1111/desc.13244
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the rule‐learning effect in 7‐month‐old infants: A close, multicenter replication of Marcus et al. (1999)

Abstract: We conducted a close replication of the seminal work by Marcus and colleagues from 1999, which showed that after a brief auditory exposure phase, 7-month-old infants were able to learn and generalize a rule to novel syllables not previously present in the exposure phase. This work became the foundation for the theoretical framework by which we assume that infants are able to learn abstract representations and generalize linguistic rules. While some extensions on the original work have shown evidence of rule le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our replication of the seminal Kovács and Mehler (2009) study stresses the importance of exact replications in the field of developmental science in multiple labs (Frank et al., 2017; Geambașu et al., 2022; The ManyBabies Consortium, 2020) in combination with more advanced statistical techniques (Bayes; Cluster‐based; logistic regression). Our inability to replicate the original findings not only for this study, but also for another infant study on rule learning (i.e., Marcus et al.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Our replication of the seminal Kovács and Mehler (2009) study stresses the importance of exact replications in the field of developmental science in multiple labs (Frank et al., 2017; Geambașu et al., 2022; The ManyBabies Consortium, 2020) in combination with more advanced statistical techniques (Bayes; Cluster‐based; logistic regression). Our inability to replicate the original findings not only for this study, but also for another infant study on rule learning (i.e., Marcus et al.…”
Section: Discussionmentioning
confidence: 61%
“…Our inability to replicate the original findings not only for this study, but also for another infant study on rule learning (i.e., Marcus et al. (1999)—see Geambașu et al., 2022) highlights the necessity of repeated replication attempts to obtain a better understanding of the factors that may or may not contribute to the building blocks of infant cognition.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The average effect size was estimated as g = 0.25, 95% CI = [0.09, 0.40] (Rabagliati et al, 2019). A recent study in 4 Dutch babylabs found no evidence for rule learning in a close replication of the original paradigm (Geambas et al, 2023).…”
Section: Illustration: Rule Learningmentioning
confidence: 85%